The Impact of Modern Technologies of Virtual Reality on the Design of Performance Auditoriums (Journal of University of Babylon for Engineering Sciences, 2018)
The research deals with the technological production, modern techniques of virtual reality, and the revolution which it created in theatre production, theatre architecture, and the creation of performance scenes. As well as its impact on the theatre building, theatre design, theatre standards, and dimensions. The research problem focused in the lack of knowledge about the impact of the introduction of modern technology of virtual reality techniques on the stage and impact on the design of the stage and the auditorium. thus, the research aims at clarifying the role of modern techniques of virtual reality, its effect on performance performances, and the design of theater, as well as its role in achieving the virtual scenes. The research suggests that modern techniques are the goal of changing some of the classical rules and regulations of various types of performance auditorium, as well as exploiting the new concepts of digital virtual presentation techniques that provide the requirements of the new stage, which became the basis of contemporary scenes. The research applied the indicators which reached from the theoretical framework on the selected case study to reach the research results. Two international projects were selected as case studies: The Crafton Preyer Theatre in Kansas, USA,  and The New World Center in Miami, USA. The research reach the importance role of modern technologies of multimedia and virtual reality as a new stenographic instrument on the stage, and its role in the development of interactive theatre performance, as well as the progress of using multimedia technologies and projection indicator on the newer technology of virtual reality use's indicator, such as hologram technology, which entered the theater in the past few decades, and it use is still limited in a number of famous theaters and auditorium around the world. But the future tends to use them on a large scale. The achievement of the research aim has necessitated the adoption of the analytical descriptive scientific method, whose structure evolves with the research result and conclusions.